Strategi Komunikasi Pemasaran dalam Membangun Loyalitas Konsumen bagi UMKM Nasi Goreng Barokah Jaya, Cikampek - Farkhan Fidaya Tulloh; Eka Anisa Sari (Journal of Management and Social Sciences, 2026)
An appropriate strategy has become a crucial factor for Micro, Small, and Medium Enterprises (MSMEs) in maintaining customer loyalty. This study focuses on analyzing the implementation of marketing communication strategies adopted by Nasi Goreng Barokah Jaya, an MSME located in Cikampek, to retain its loyal customers. This study employed a descriptive qualitative approach based on the 7P Marketing Mix theory developed by Kotler and Keller (2016). Data were collected through in-depth interviews, field observations, and documentation involving the business owner, employees, and loyal customers. The data were subsequently analyzed using the Miles and Huberman interactive model, while data validity was ensured through triangulation. The findings reveal that direct interaction, responsive and friendly service, word-of-mouth promotional activities, and personalized approaches serve as the main pillars in building customer loyalty. Customer loyalty is significantly influenced by product quality, price affordability, service reliability, and the emotional bond established between the business and its customers. These findings confirm that simple yet consistently implemented marketing communication strategies are effective in maintaining a loyal customer base in the culinary MSME sector.